Ad hoc and proactive approaches of older adults to daily memory problems - Konieczna, Agnieszka; Żak, Monika (Adult Education Discourses, 2025)
The study focuses on the strategies and resources utilized by older adults in response to everyday memory challenges. A phenomenographic methodology was employed to conduct interviews with 14 community-dwelling older adults, some of whom participated in cognitive or recreational stimulation programs at local senior clubs. The findings indicate that participants used a wide range of compensatory strategies, primarily simple, intuitive memory-supporting methods integrated into their daily lives. However, they rarely sought professional support, and their openness to new approaches was limited. Even those engaged in community-based programs were aware of the theoretical benefits of lifestyle management but implemented these recommendations to a limited extent. The study also discusses challenges related to the adoption of health-promoting strategies and factors influencing seniors’ engagement in preventive activities. A key factor was their need to maintain independence and their belief that their existing methods were sufficient. The results highlight the necessity of developing more holistic support strategies that better address the diverse needs of older adults while respecting their desire for agency and autonomy in health-related decision-making. Adopting a lifelong cognitive development approach may contribute to more effective long-term interventions.